Analisis Pendidikan Karakter Era Digital melalui Perspektif Filosofi Pendidikan Ki Hajar Dewantara di Indonesia - Hilda Triyaswati (Universitas Insan Budi Utomo, 2024)
Character education is crucial in building moral principles and accountability. Ki Hajar Dewantara's educational philosophyemphasises holistic individual development through three educational disciplines - Ing Ngarso Sung Tulodo, Ing Madya Mangun Karso, and Tut Wuri Handayani. Along with the ideals of the Indonesian nation to educate the nation's life, education is a very important aspect. Although education in Indonesia has progressed, one of the current obstacles related to character education hasnot reflected the ethical cultural values of the Indonesian nation. This analysis highlights the importance of understanding character education, highlights the difficulties in integrating moral principles as digitalisation develops, and reviews the application of Ki HajarDewantara's philosophy in the digital era. This research reviews Dewantara's values approach to improving character education inIndonesia as well as building a moral and ethical society in the contemporary era through a literature review.